The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.leu.2404689
|View full text |Cite
|
Sign up to set email alerts
|

Junctional adhesion molecule C (JAM-C) distinguishes CD27+ germinal center B lymphocytes from non-germinal center cells and constitutes a new diagnostic tool for B-cell malignancies

Abstract: Differentiation of naive B cells into plasma cells or memory cells occurs in the germinal centers (GCs) of lymph follicles or alternatively via a GC- and T-cell-independent pathway. It is currently assumed that B-cell lymphomas correlate to normal B-cell differentiation stages, but the precise correlation of several B-cell lymphomas to these two pathways remains controversial. In the present report, we describe the junctional adhesion molecule C (JAM-C), currently identified at the cell-cell border of endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…We had previously reported that the expression of JAM-C in B-cell lymphomas revealed a disease-specific pattern, distinguishing JAM-Cpos from JAM-Cneg B-cell lymphomas (13). In Fig.…”
Section: Homing Of Malignant Lymphoma B Cells To Lymphoid Organs Is Bmentioning
confidence: 81%
See 3 more Smart Citations
“…We had previously reported that the expression of JAM-C in B-cell lymphomas revealed a disease-specific pattern, distinguishing JAM-Cpos from JAM-Cneg B-cell lymphomas (13). In Fig.…”
Section: Homing Of Malignant Lymphoma B Cells To Lymphoid Organs Is Bmentioning
confidence: 81%
“…Cells were stably transfected using Amaxa Nucleofection System according to manufacturer's instructions with a pcDNA plasmid encoding a neomycin-resistance cassette without (¼pcDNAe) or with full-length human JAM-C cDNA (¼HuJAM-C; ref. 13). After 2 weeks selection with G418, 1 mg/mL (Invitrogen) cells were fluorescence-activated cell sorting (FACS)-sorted and further expanded under G418 selection (600 mg/mL).…”
Section: Transfection Of Jam-cneg Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have shown that JAM-C is expressed on dendritic cells, platelets, and subsets of T and B cells in humans. 23,39,41,43,44,69 To date, however, JAM-C expression has not been reported on mouse leukocytes. 48 The pan-expression of human JAMs across leukocyte and endothelial/epithelial populations has introduced a further level of complexity to interpreting a precise role for these molecules in leukocyte trafficking.…”
Section: Jam-c Expression On Leukocytes: a Junctional Affair?mentioning
confidence: 99%